The Impact Of Financial Liberalization On Economic Risk In The Asia Pacific Countries - Aulia Keiko Hubbansyah; Feriansyah Feriansyah (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2020)
In this study, we analyze the non-linear effect of financial liberalization policy toward the economic risk of the Asia Pacific countries with trade openness as a threshold variable. To do that, we apply the panel regression threshold proposed by Hansen (1999) as our method of analysis. Based on yearly data from 1975 – 2015, we find that there is a non-linear effect of financial liberalization on economic risk depending on the certain level of trade openness. Regarding this finding, we find that when the trade openness is below the threshold value, financial liberalization policy can reduce the economic risk of Asia Pacific countries. However, when the trade openness exceeds the threshold value, financial liberalization will increase the economic risk. So that, we conclude that an open domestic financial market that is followed by high degree of trade openness will tend to create an economic instability. Keywords: Financial Liberalization, Trade Openness, Economic Risk, Volatility